2008
DOI: 10.4049/jimmunol.180.2.800
|View full text |Cite
|
Sign up to set email alerts
|

CpG Drives Human Transitional B Cells to Terminal Differentiation and Production of Natural Antibodies

Abstract: The receptor TLR9, recognizing unmethylated bacterial DNA (CpG), is expressed by B cells and plays a role in the maintenance of serological memory. Little is known about the response of B cells stimulated with CpG alone, without additional cytokines. In this study, we show for the first time the phenotypic modification, changes in gene expression, and functional events downstream to TLR9 stimulation in human B cell subsets. In addition, we demonstrate that upon CpG stimulation, IgM memory B cells differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
215
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(230 citation statements)
references
References 55 publications
10
215
2
3
Order By: Relevance
“…However, various studies have shown that PPS induce efficient activation of IgM + memory B cells (IgM + IgD + CD27 + ) and generation of long-lived plasma cells (CD38 + CD20 low ). This is accompanied by the generation and persistence of IgM and IgG antibodies against PPS [101][102][103][104][105][106][107][108]. IgM + memory B cells circulating in the blood are the peripheral correlates of the marginal zone B cells of the spleen.…”
Section: Immunogenicitymentioning
confidence: 99%
“…However, various studies have shown that PPS induce efficient activation of IgM + memory B cells (IgM + IgD + CD27 + ) and generation of long-lived plasma cells (CD38 + CD20 low ). This is accompanied by the generation and persistence of IgM and IgG antibodies against PPS [101][102][103][104][105][106][107][108]. IgM + memory B cells circulating in the blood are the peripheral correlates of the marginal zone B cells of the spleen.…”
Section: Immunogenicitymentioning
confidence: 99%
“…The mechanisms underlying this condition are poorly known. In this context, of particular interest is the observation that transitional B cells stimulated by CpG terminally differentiate into plasma cells producing natural antibodies with innate pneumoccoccal specificity (42). It has been recently shown that TLR9 responsiveness to CpG stimulation is diminished in HIV-1 disease (43).…”
Section: Figmentioning
confidence: 99%
“…Compared with naïve or FO B cells, MZ B cells exhibit increased expression of costimulatory receptors, including complement receptor 2 and additional Toll-like receptors (TLRs) (48)(49)(50)(51). Human MZ B cells respond more robustly to Tcell-like help or TLR stimulation in vitro (52)(53)(54)(55). Rodent MZ B cells express CD1d, and human MZ B cells express CD1c (19), allowing these cells to provide cognate help to a wider range of T cells compared with FO B cells.…”
Section: Discussionmentioning
confidence: 99%